Rancang Bangun Aplikasi Video Streaming pada Portable · wireless dengan P latform Real Network - Wahyuningrum, Rima Tri (Universitas Trunojoyo Madura, 2008)
This paper would implement a video streaming application at wireless network. Before, it worked, main problem at wireless network is bandwidth. Special qualityfrom Real Network platform was be available facility at encoder side in which we could manage bandwidth that we need was suitable with network. Measurement in three places were city center with average power level -65 dbm, sub-urban with average power level -66 dbm and village with average power level-95 dbm, gave data for consideration matter at analysis video streaming that represent reality condition infield.